Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given that $x^n + y^n = 1$, show that $$\frac{d^2y}{dx^2} = -\frac{(n-1)x^{n-2}}{y^{2n-1}}.$$

I found that $\displaystyle nx^{n-1}+ny^{n-1}\frac{dy}{dx} = 0$ so that $\displaystyle y'=\frac{-x^{n-1}}{y^{n-1}}$.

Then $$n(n-1)x^{n-2}+n(n-1)y^{n-2}\left(\frac{dy}{dx}\right)^2 + \frac{d^2y}{dx^2}ny^{n-1} = 0.$$

Therefore $$y'' = \displaystyle \frac{-n(n-1)x^{n-2}-n(n-1)y^{n-2}(y')^2}{ny^{n-1}}.$$

Substituting the first derivative:

$$y'' = \displaystyle\frac{-n(n-1)x^{n-2}-n(n-1)y^{n-2}\left(\dfrac{-x^{n-1}}{y^{n-1}}\right)^2}{ny^{n-1}}.$$

I've been trying tons of different steps and can't establish which way to eliminate the $y$ terms from the numerator. Could someone offer a hint on how to proceed. Thanks.

share|cite|improve this question
up vote 2 down vote accepted

Expanding your final expression, we have

\begin{align*} y'' &= \frac{-n(n-1)x^{n-2} -n(n-1)y^{n-2}\dfrac{x^{2n-2}}{y^{2n-2}}}{ny^{n-1}}\\ &= \frac{-n(n-1)x^{n-2} -n(n-1)y^{-n}x^{2n-2}}{ny^{n-1}}\\ &= \frac{-n(n-1)x^{n-2}(1 + x^{n}y^{-n})}{ny^{n-1}}\\ &= \frac{-(n-1)x^{n-2}(1 + x^{n}y^{-n})}{y^{n-1}}. \end{align*}

Now note that $x^n + y^n = 1$, so $x^ny^{-n} + 1 = y^{-n}$. Therefore

\begin{align*} y'' &= \frac{-(n-1)x^{n-2}(1 + x^{n}y^{-n})}{y^{n-1}}\\ &= \frac{-(n-1)x^{n-2}y^{-n}}{y^{n-1}}\\ &= \frac{-(n-1)x^{n-2}}{y^{2n-1}}. \end{align*}

share|cite|improve this answer
I just realised the question asked for a hint. Sorry user90771. – Michael Albanese Sep 1 '13 at 12:39
It doesnt matter, I was doing it correct all the way till the last line. The thing Im not understanding is how you divided the $y^{-n}$ with the $y^{n-1}$. thanks! – salman Sep 1 '13 at 12:41
Do you mean how do I go from $\dfrac{y^{-n}}{y^{n-1}}$ to $\dfrac{1}{y^{2n-1}}$? – Michael Albanese Sep 1 '13 at 12:43
yeah, I know that if we have $$\frac{y^{-n}}{y^{n-1}} = y^{-n-n+1} = y^{-2n+1}$$ But how have you done this step? – salman Sep 1 '13 at 12:44
So are you still not understanding something or have you got it? – Michael Albanese Sep 1 '13 at 12:45






Should be easy from there.

share|cite|improve this answer

Differentiating $y^{n-1}y_1+x^{n-1}=0$ wrt $x,$

$\displaystyle y^{n-1}y_2+(n-1)y^{n-2}y_1^2+(n-1)x^{n-2}=0$

$\implies \displaystyle -\frac{y^{n-1}y_2}{n-1}=x^{n-2}+y^{n-2}\left(-\frac{x^{n-1}}{y^{n-1}}\right)^2$ as $y_1=-\frac{x^{n-1}}{y^{n-1}}$

$$\implies -\frac{y^{n-1}y_2}{n-1}=x^{n-2}+\frac{x^{2n-2}}{y^n}=\frac{x^{n-2}(y^n+x^n)}{y^n}=\frac{x^{n-2}}{y^n}\text{ as } y^n+x^n=1$$

share|cite|improve this answer
@user90771, how about this method? – lab bhattacharjee Sep 1 '13 at 13:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.